(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Software testing is a very broad area, which involves many other technical and non-technical areas, such as specification, design and implementation, maintenance, process and management issues in software engineering. This report provides an automated approach to select test cases for object oriented program by using genetic algorithm. The given approach takes less time and meets adequacy criteria for example coverage. There are many approaches available for automatic selection of test cases for procedural pro- gram but the selection of test cases for object oriented program is challenging. The pro- posed approach enhances the previously available approaches and shows the good result.